2022
DOI: 10.1093/stcltm/szab028
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Therapies for Limbal Stem Cell Deficiency

Abstract: The corneal epithelium serves to protect the underlying cornea from the external environment and is essential for corneal transparency and optimal visual function. Regeneration of this epithelium is dependent on a population of stem cells residing in the basal layer of the limbus, the junction between the cornea and the sclera. The limbus provides the limbal epithelial stem cells (LESCs) with an optimal microenvironment, the limbal niche, which strictly regulates their proliferation and differentiation. Distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 112 publications
0
16
0
Order By: Relevance
“…Allogenic limbal grafts are the mainstay for the treatment of bilateral total LSCD, such as kerato-limbal allograft (cadaveric donor) and living related conjunctival limbal allograft (with some risk of causing LSCD in the donor's eye). 5,6 Like ours, most ophthalmology centers do not have the technology to perform LSC culture and transplantation, which would have been a good option for our patient. 7 Nevertheless, there are limitations of LSC transplantation, particularly in bilateral LSCD cases, as both techniques require immunosuppression, and success rates vary between 33% to 77%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Allogenic limbal grafts are the mainstay for the treatment of bilateral total LSCD, such as kerato-limbal allograft (cadaveric donor) and living related conjunctival limbal allograft (with some risk of causing LSCD in the donor's eye). 5,6 Like ours, most ophthalmology centers do not have the technology to perform LSC culture and transplantation, which would have been a good option for our patient. 7 Nevertheless, there are limitations of LSC transplantation, particularly in bilateral LSCD cases, as both techniques require immunosuppression, and success rates vary between 33% to 77%.…”
Section: Discussionmentioning
confidence: 90%
“…7 Nevertheless, there are limitations of LSC transplantation, particularly in bilateral LSCD cases, as both techniques require immunosuppression, and success rates vary between 33% to 77%. 5,8 Holoclar ® , a stem-cell treatment, requires healthy cells from the patient's limbus. 6 Other non-limbal autologous sources of grafts include cultivated oral mucosal epithelial transplantation and autologous conjunctival epithelial transplantation, but both have been associated with corneal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the benefits of autologous LSC transplantation over allogeneic limbal transplantation, methodologies for autologous transplantation in patients who do not have a healthy reservoir of LSCs are urgently needed. Moreover, allogeneic limbal grafts are often scarce, further limiting this transplantation option [ 83 ]. Transdifferentiation of a different stem cell line is one therapeutic avenue that may allow clinicians to avoid allogeneic transplantation in bilateral complete LSCD ( Table 3 ).…”
Section: Future Directions: Modulation Of Non-limbal and Limbal Stem ...mentioning
confidence: 99%
“…Transdifferentiation of a different stem cell line is one therapeutic avenue that may allow clinicians to avoid allogeneic transplantation in bilateral complete LSCD ( Table 3 ). In the early 2000s, transplantation of cultivated oral mucosa epithelium was found to recapitulate corneal epithelium development in [ 58 ], but further research since then has demonstrated that persistent oral epithelium morphology hampers post-transplantation visual outcomes [ 83 , 84 , 85 ]. Stem cells derived from hair follicle, pluripotent, dental pulp, and umbilical cord sources have been shown to transdifferentiate into corneal epithelium-like cells when exposed to the limbal niche in vitro and in animal models, but related clinical trials have been limited [ 86 , 87 , 88 , 89 , 90 ].…”
Section: Future Directions: Modulation Of Non-limbal and Limbal Stem ...mentioning
confidence: 99%